2023
DOI: 10.3389/fped.2023.1180068
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital growth and long-term neurodevelopmental outcomes of very low birth weight infants

Alessandra Consales,
Matteo Porro,
Silvana Gangi
et al.

Abstract: Background and ObjectivesVery low birth weight infants (VLBW) are at risk for adverse growth and neurodevelopmental outcomes. We aimed to evaluate the association between growth during Neonatal Intensive Care Unit (NICU) stay and long-term neurodevelopmental outcomes in a cohort of preterm VLBW newborns.MethodsWe conducted a longitudinal observational study in the Follow-up Service of our Clinic from January 2014 to April 2017. All preterm VLBW infants born at our hospital and enrolled in our follow-up program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…(6)(7)(8)(9) Additionally, investigations have revealed the relationship between postnatal growth and long-term neurodevelopmental outcomes in ELBW infants, emphasizing the lasting consequences of growth challenges. (10)(11)(12)(13)(14) Variable degrees of catch-up were reported by different authors at different times postnatally. For instance, Raaijmakers et al conducted a comprehensive study that examined the postnatal growth patterns of ELBW infants for 11 years and identified that Catch-up growth (i.e., ΔZ-score >0.67 SDS) for weight was achieved during the first two years of life in only 9.9% of cases, for length in 13.7% of cases and for head circumference in 14.1% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…(6)(7)(8)(9) Additionally, investigations have revealed the relationship between postnatal growth and long-term neurodevelopmental outcomes in ELBW infants, emphasizing the lasting consequences of growth challenges. (10)(11)(12)(13)(14) Variable degrees of catch-up were reported by different authors at different times postnatally. For instance, Raaijmakers et al conducted a comprehensive study that examined the postnatal growth patterns of ELBW infants for 11 years and identified that Catch-up growth (i.e., ΔZ-score >0.67 SDS) for weight was achieved during the first two years of life in only 9.9% of cases, for length in 13.7% of cases and for head circumference in 14.1% of cases.…”
Section: Introductionmentioning
confidence: 99%